Kecenderungan perilaku cyberbullying pada remaja SMA: Bagaimana peranan konformitas teman sebaya? - Rista Ristiani; Eko April Ariyanto; Etik Darul Muslikah (INNER: Journal of Psychological Research, 2023)
This study was conducted with the purpose of knowing the relationship between peer conformity and the tendency of cyberbullying behaviour in high school adolescents. Respondents in this study were 140 high school students with data collection using questionnaires. This study uses two scales, the conformity scale and the cyberbullying scale. The data collection instrument in this study uses a Likert scale model. The sampling technique used in this study used a saturated sampling technique. Data analysis was conducted in this study using the product-moment correlation method with the help of statistical product and service solution (SPSS) version 26.0 for Windows. The results of this study indicate that there is no correlation between conformity behaviour and the tendency of cyberbullying behaviour, so the lower the conformity behaviour, the lower the tendency of cyberbullying behaviour in adolescents.